Level Of Self-efficacy Among Football Players Between 16 -19 Old Years - Kenioua, Mouloud (sports creativity, 2025)
The study aimed to determine the level of self-efficacy among football players aged 16-19 and to examine self-efficacy levels among football players based on their playing positions. The sample consisted of 61 amateur football players aged 16 to 19. The Schwarzer Self-Efficacy Scale (GSES) was used to collect data. Descriptive statistics, specifically the Kruskal-Wallis test, were also employed. The results indicated a high level of self-efficacy among the football players and showed no statistically significant differences based on their playing positions.